Brewing Connections: Socio-Cultural Engagement and Intercultural Communication Exchanges in Contemporary Bruneian Cafés - Muhammad Afiq Azwar Muhammad Anwar; Nena Padilla-Valdez (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2026)
This Study explored how the evolving characteristics of Bruneian cafes provide inclusive avenues for community and cultural experiences among consumers. Specifically, it charted a comprehensive narrative of contemporary cafe environments as informal communicative spaces that facilitate social integration, cultural connection, and potential wellbeing. Context sensitivity driven, the study adopted snowball sampling to determine the participants. Data were collected through semi-structured interviews and on-site observations including artefact documentation in order to capture rich and naturally occurring exchanges within cafe settings. The findings disclosed three key themes: cultural diversity, community belonging, and spatial preferences for choosing cafes as platforms for intercultural connections, other factors such as affordability, existing social structures, and comfort zones emerged as essential considerations inclusivity. Overall, the study highlights the potential for a broader understanding of the evolving nature of intercultural relational exchanges and contemporary cultures in Brunei.